The Knee-SCHOOL: a brief patient-centered multidisciplinary educational program for knee osteoarthritis - Ayres, Denise Vianna Machado; Uchiyama, Sabrina Saemy Tome; Prates, Andréa Oliveira; Lopes, Rosana Aparecida Freitas; Silva, Antenor Bispo Santos; Tsukimoto, Denise Rodrigues; Amorim, Rosimeire Alves; Ribeiro, Taynah Souza; Santos, Artur Cesar Aquino; Sugawara, André Tadeu; Montagnini, Marcos; Battistella, Linamara Rizzo; et al. (Frontiers in Medicine, 2025)
BackgroundKnee osteoarthritis (KOA) is the most common form of arthritis in adults and a leading cause of years lived with disability, representing a significant burden on healthcare worldwide.ObjectiveDescribe the structure and educational elements of the Knee-SCHOOL, a brief patient-centered multidisciplinary educational program for patients with KOA.DesignObservational prospective study.SettingAcademically affiliated rehabilitation outpatient center in Brazil.MethodsThe program consisted of three in-person educational sessions (4.5 hr each) for 55 community dwelling adults, aged ≥50 years, with primary KOA-related pain. Study measures included demographic data (age, sex, and educational level), pain duration (years), pain intensity (visual analogue scale), affected knee (right, left, or both knees), comorbidities (presence of hypertension, diabetes, and hypercholesterolemia), Body Mass Index (BMI), Bristol Stool Scale, Adapted Healthy Eating Index (AHEI), bioelectrical impedance, daytime sleepiness, and the impact of the KOA on pain, symptoms, activities of daily living, recreation, and quality of life. Participants attended educational sessions delivered by a multidisciplinary team (two physicians, two nurses, two physical therapists, one occupational therapist, one dietitian, one psychologist, one social worker, and one physical educator) addressing several aspects of KOA. They also participated in supervised exercise practice and a home exercise program.ResultsFifty-five subjects completed the study. The mean age was 67.73 (± 7.73) years; most were females (70.9%), 92.7% had bilateral KOA, with mean pain duration of 12.41 (± 10.17) years. The mean BMI was 32.52 (± 5.99), 65.5% were obese, and 96.4% reported an inadequate diet. KOA had a more negative impact on sports, recreation and quality of life. Daytime sleepiness was uncommon. The mean pain intensity, measured with visual analogue scale, score reduced from 5.52 (± 2.11) at baseline to 4.04 (± 2.38) after the program (week 2). The effect size was 0.7 (95% CI 0.32 to 1.07). All participants received the program well, with no drop-out rates or reported adverse events.ConclusionThe Knee-SCHOOL utilized a multidisciplinary educational approach and an exercise practice addressing multiple aspects of KOA pain. While more studies are needed to assess the longitudinal impact of the program, it was promising in managing pain.